Pengaruh Marketing Activity Terhadap Profitability dan Market Value Perusahaan Retail dan Produksi Besar - Trisnawati Debora (Business Accounting Review, 2015)
This study aimed to examine the affect of Marketing Activity which is consist of Marketing Expense, Company Age, and Company Size partially and simultaneously to Profitability represented by Return on Sales, Return on Asset, Return on Equity, and to Market Value represented by Earning per Share, Market to Book Value Ratio, Tobin’s Q. This study used annual report of Retail and Large Production Companies listed in BEI from 2009-2013 as the secondary data. The samples used in this study were 15 retail and 16 large production companies. The results showed that Marketing Expense, Company Age, and Company Size influenced ROS, ROA, and EPS significantly positive. Company Age influenced ROS and ROE significantly negative and influenced MBVR and Tobin’s Q significantly positive. Company Size only influenced ROA and EPS.